Entrepreneurship in Africa : context and perspectives - Sriram, Ven; Lingelbach, David, 1961-; Mersha, Tigineh, 1946-; Manu, Franklyn, 1956- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"It is now widely recognised that in regions like Africa, for economic and other reasons, the public sector has had to transition away from several areas of the economy and allow private enterprise, especially scalable start-ups and new ventures, to enter and flourish if economic development and employment are to grow. There is, however, a training and education gap since entrepreneurship is rarely taught formally at African universities and, when it is, it is often approached from a Western perspective that may not be appropriate given that African environments are significantly different from most Western ones in terms of economic infrastructure and political considerations. This book allows readers to the understand the African entrepreneurial context by guiding them through the principal stages in the life of a new venture, and offers approaches, both Western and indigenous, that can inform their entrepreneurial actions. It concludes by examining some specialised topics, including female, youth and social entrepreneurship, as well as real estate and technology. Exercises throughout the book will enable readers to evaluate their motivations and preparedness for entrepreneurship and learn how to communicate a new venture's key features to potential stakeholders. By focusing on the distinctive features of entrepreneurship in the African context, and taking a conversational tone, this is an informative and practical text that will be useful for students of Global Entrepreneurship and Business as well as actual and prospective entrepreneurs in the private, non-profit and public sectors"--
The African Environment for Entrepreneurship -- Theories of Entrepreneurship -- Mindset, Capabilities and Goals -- Financing the Venture -- The Marketing Imperative -- Operations and Supply Chain Management -- Managing Networks and Teams -- Appendices to Part III: Business Plans and Pitch Decks -- Next Steps -- African Women Entrepreneurs -- Entrepreneurial Opportunities in Real Estate Development -- Understanding Entrepreneurs: A Focus on Youth -- Technologies Enabling Entrepreneurship in Africa.
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship -- Africa; New business enterprises -- Africa; New business enterprises -- Africa -- Finance; New business enterprises -- Africa -- Management; BUSINESS & ECONOMICS / Entrepreneurship